2009
DOI: 10.1515/integ.2009.031
|View full text |Cite
|
Sign up to set email alerts
|

φ(Fn ) = Fm

Abstract: We show that 1, 2 and 3 are the only Fibonacci numbers whose Euler functions are also Fibonacci numbers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…where T 2 and T 3 denote the sums of the reciprocals of the primes in P n satisfying (ii) and (iii), respectively. The sum T 2 was estimated in [10] using the large sieve inequality of Montgomery and Vaughan [13] (see also page 397 in [11]), and the bound on it is (2.11)…”
Section: The Binet Formula Formentioning
confidence: 99%
See 3 more Smart Citations
“…where T 2 and T 3 denote the sums of the reciprocals of the primes in P n satisfying (ii) and (iii), respectively. The sum T 2 was estimated in [10] using the large sieve inequality of Montgomery and Vaughan [13] (see also page 397 in [11]), and the bound on it is (2.11)…”
Section: The Binet Formula Formentioning
confidence: 99%
“…therefore, q 1 < k(P n /P n−1 ) < 3k. Using the method of the proof of inequality (13) in [11], one proves by induction on the index i ∈ {1, . .…”
Section: Bounding the Primes Qmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the most familiar arithmetic functions in number theory are: The study of arithmetic functions of a linearly recurrent sequence has been a popular area of research. For example, in [10] it was shown that 1, 2, and 3 are the only Fibonacci numbers whose Euler function is also a Fibonacci number, while in [3] it was proved that if {u n } n≥0 is a Lucas sequence with b ∈ {±1}, then there are only finitely many effectively computable n such that φ(|u n |) is a power of 2, extending the previous works [8,12] which dealt with the above problem for the particular Lucas sequences of the Fibonacci and Pell numbers. In [9] it was shown that the largest Fibonacci number whose Euler function is a repdigit (i.e., numbers with only one distinct digit in its decimal expansion) is F 11 for which φ(F 11 ) = 88, while in [11] it was proved that there are no repdigits with two or more digits which are multiply perfect, namely numbers who divide the sum of their divisors.…”
Section: Introductionmentioning
confidence: 99%